The Effectiveness Of Internally Implanted Heat Sources In The Treatment Of Brain Tumors Numerical Simulation Of Right Lobe Peripheral Brain Tumor Treatment (Damascus University Journal for engineering sciences, 2023)
In this paper, we present a simulation of heat therapy for brain cancer using internal micro-sources, by studying a peripheral brain tumor model. Where a three-dimensional model of the tumor was built based on the medical images taken from an axial tomography device, and then these images were exported to a simulation program for thermal mapping during treatment, using two different energies of internal sources, 195000 W/m3 and 37900 W/m3 with different times for treatment application are 300s,600s,900s..The study concluded that the treatment method used is highly effective in killing cancer cells while achieving a great safety ratio for healthy tissues, as treatment with internal heat sources is a promising treatment if micro-simulation is used and the energy sources and treatment time are controlled accurately.
Keywords: Cancer; Heat Treatment; Internal Sources; Brain